Health Literacy as a Public Health Priority in Crisis Management: Strategies and Policy Recommendations - Nirwan, Multy Syaddam (Yayasan Sinergi Kawula Muda, 2023)
Health literacy is a critical determinant of crisis preparedness, influencing how individuals access, comprehend, and utilize health information during emergencies. This study systematically reviews the role of health literacy in emergency preparedness and response, examining its impact on individual decision-making, community resilience, and public health interventions. A comprehensive literature search was conducted across academic databases, including PubMed, Scopus, and Google Scholar, focusing on studies published from 2018 onward. Findings indicate that higher health literacy levels enhance adherence to emergency health guidelines, facilitate risk perception, and contribute to better health outcomes. However, disparities in health literacy—shaped by socioeconomic inequalities, digital accessibility, and misinformation—continue to pose challenges in crisis management. The study highlights the increasing role of digital health communication and social media in disseminating health information, emphasizing the need for regulatory measures to counteract misinformation. Policy recommendations include integrating health literacy into public health strategies, enhancing community-driven education initiatives, and leveraging digital health tools for widespread information dissemination. Future research should explore the effectiveness of tailored interventions in marginalized communities and the long-term impact of digital health literacy initiatives. By prioritizing health literacy in crisis management frameworks, policymakers can improve population-level health resilience and ensure equitable access to critical health information.